Thermal relaxation processes in some organic liquids - Zygmunt KLESZCZEWSKI (Archives of Acoustics, 2016)
Measurements of propagation velocity and absorption coefficient of acoustic waves in some organic liquids have been made for frequencies between 106 Hz and 5 x 109 Hz at 20°C. On the basis of the data obtained the problem of thermal relaxation in liquids examined has been discussed. It was found that this process cannot be described by the relaxation time, which means that at a given fre¬quency only some of internal degrees of freedom undergo excitation. Tests have been undertaken aimed at estimating which of the said degrees of freedom take an active part in the process of energy exchange.